IMPACT ANALYSIS OF IMPELLER PARAMETERS ON THE WIND-ENERGY UTILIZATION COEFFICIENT OF VERTICAL AXIS WIND TURBINE - HU Cao Di; WANG ChangLu; WEI LeYu; QIAO XueTao (Jixie qiangdu)
In order to have a better research on the effect factors of the vertical axis wind turbine wind-energy utilization coefficient,based on the multi-blade element momentum theory a Double Disk Multi-tube Model was established,and through mathematical modeling method to focus on the influence of chord length,radius and number of blades. Because of the loading on the wind turbine during rotation was complex,the rotation plane was divided into four quadrants,and put forward the fourquadrant analysis method on the basis of the original theory,then established the simulation model based on the analysis of stress. Finally,in view of the NACA0018 airfoil,study respectively in different chord length,impeller radius and number of blades using the four-quadrant analysis method,the change of vertical axis wind turbine wind-energy utilization coefficient,which provides a reference for the selection of fan impeller parameters.